Putative Markers of Repression in Patients Suffering From Mental Disorders - Kehyayan, Aram; Matura, Nathalie; Klein, Kerstin; Schmidt, Anna-Christine; Herpertz, Stephan; Axmacher, Nikolai; Kessler, Henrik (Frontiers in Psychology, 2018)
Background The concept of psychodynamic conflict is essential to psychodynamic theory and therapy. In classical psychodynamic therapy, unconscious conflict themes need to be identified by the therapist and brought to the patient’s awareness, in order to work through and ultimately solve them. According to theory, touching upon conflict-related topics leads to arousal, followed by activation of defense mechanisms such as repression. Starting with C.G. Jung’s association studies more than 100 years ago, various proposals have been made to investigate psychodynamic conflicts based on free association and psychophysiological measures. This study presents an attempt to identify and differentiate between psychodynamic conflict themes in patients, using an adopted version of Jung’s paradigm that had in previous studies been applied to healthy subjects. Method 17 patients suffering from depression and other mental disorders associated freely to different cue sentences. Prior to the experimental procedure, patients’ individual psychodynamic conflict types were assessed through clinical interviews. Sentences were either neutral, negative (but not conflict-related), or related to specific types of psychodynamic conflicts. Memory for the first three associations was later tested in an unexpected recall task. Skin conductance response (SCR) was recorded and analyzed together with reaction times (RTs) and self-ratings of emotional valence, arousal, and agreement with cue sentences. Results Patients showed reduced memory performance for associations to conflict-related sentences in general, compared with negative and neutral sentences. Agreement with conflict-related sentences was lower compared to neutral but not negative sentences. Memory was negatively correlated with RTs and SCR. RTs were longer for conflict types that had been rated as relevant in clinical interviews prior to the association task, compared to the other, non-relevant conflict types. Conclusion Our study shows that some putative markers of repression of psychodynamic conflicts previously established in healthy participants also occur in patients. Moreover, it provides evidence that general conflict effects differ from specific effects of personally relevant conflicts.